A Cisplatin‐Loaded Immunochemotherapeutic Nanohybrid Bearing Immune Checkpoint Inhibitors for Enhanced Cervical Cancer Therapy. (27th February 2018) - Wang, Na; Wang, Zhigang; Xu, Zoufeng; Chen, Xianfeng; Zhu, Guangyu
Abstract: The efficacy of conventional chemotherapy is hindered by cancer cell escape from the immune system. A multifunctional nanohybrid system is reported for effective immunochemotherapy against cervical cancer. This nanohybrid contains both immune checkpoint inhibitor and cisplatin anticancer prodrug, showing improved cellular accumulation and increased binding of Pt to DNA and resulting in elevated apoptosis than using cisplatin alone when tested in cervical cancer cells. The immune checkpoint inhibitor enables the inhibition of indoleamine‐2, 3‐dioxygenase and reverses immunosuppressive T cells to recognize cancer cells, leading to T cell proliferation and activation, cancer cell cycle arrest, and ultimately increased cancer cell death. The nanohybrid is also active in vivo against the growth of human cervical tumors. Overall, a strategy is provided using a multifunctional nanohybrid system to boost the antitumor activity of cisplatin.